Terrains and Landscapes of Urban Politics. - Fisker, Jens Kaae (Palgrave Macmillan, 2019)
The author pulls urban politics into explicit attention by exploring how the "terrains of urban politics" can be put to work as a trope whose attendant spatial imaginary is conducive to differential urban becomings.
Keywords: Stadtforschung; Stadttheorie; Stadtpolitik; Metapher; Raum; Urbanität; Differenz; Konflikt